Global trends and patterns in cardiovascular disease burden attributable to low physical activity: A systematic analysis for Global Burden of Disease Study from 1990 to 2021 - Rongxiang Zhang; Siyue Fan; Chenyang Zhu; Shiqi Chen; Feng Tian; Pingping Huang; Yuan Chen (PLoS ONE, 2025)
Background This study analyzes the global burden of cardiovascular diseases (CVD) related to low physical activity from 1990 to 2021, focusing on spatiotemporal changes. Method Using data from the GBD study, we examined trends in CVD burden linked to low physical activity, including mortality counts, disability-adjusted life years (DALYs), age-standardized mortality rates (ASMR), and age-standardized disability rates (ASDR). Decomposition analysis was used to identify key drivers of these changes, and frontier analysis visualized each country's potential to reduce the burden. An autoregressive integrated moving average model was used to forecast the burden from 2022 to 2036. Results In 2021, approximately 370,000 deaths globally were attributed to CVD due to low physical activity. The ASMR and ASDR for CVD were 4.53 per 100,000 (95% uncertainty interval: 1.52 to 8.05) and 85.95 (95% UI: 35.25 to 140.65), respectively. From 1990 to 2021, the global burden increased, particularly in regions with a middle socio-demographic index, driven by aging populations and population growth. The ASMR is projected to decrease to 3.49 per 100,000 by 2036. Conclusions Low physical activity is a major contributor to CVD-related mortality and disability worldwide. Public health interventions aimed at increasing physical activity, especially in regions with rising burdens, are essential to reduce the global CVD burden.